CONSTRUCTING ICT COMPETENCE OF PRE-SERVICE EFL TEACHERS THROUGH BLENDED LEARNING APPROACH - Rizki Farani; Egista Pregi Fatimaghribi (Fakultas Seni Rupa dan Desain ITB, 2019)
This research is to evaluate the use of blended learning in English Language Education Program, University of Islam Indonesia. The aim of this research is to describe and evaluate the implementation of blended learning to enhance ICT competence of pre-service EFL teachers in developing instructional media. The research involved 125 pre-service English teachers in Learning, Media and Technology course. During the course, blended learning process was divided into offline meeting for theoretical discussion and media project consultation; and online meeting for material designing and practicum. The data, obtained from March 2018 to April 2018, present several information; a) the analysis of students' achievements; b) the analysis of students' media project and c) document analysis (lesson plan). All data were analyzed by using instructional design and multimedia rubrics in quantitative scales. The results show that most of the students are able to develop appropriate instructional media for English learning. However, some students need more instruction to enhance their understanding during online meeting. The implication of this research is it is challenging to use blended learning for project-based assignment so educators should design balanced activity between practicum and consultation to assist students in developing their project. Keywords: blended learning, pre-service teachers, instructional media for ELT